Mannitol vs. methacholine in the evaluation of airway responsiveness in bakers’ asthma - Nowakowska-Świrta, Ewa; Wiszniewska, Marta; Lipińska-Ojrzanowska, Agnieszka; Walusiak-Skorupa, Jolanta (International journal of occupational medicine and environmental health, 2020)
Various indirect or direct airway challenge tests are used to measure nonspecific bronchial hyper-responsiveness (NSBHR). The evaluation of NSBHR in diagnosing occupational asthma (OA) is performed, e.g., to monitor the specific inhalation challenge test (SICT). The aim of this study was to preliminarily compare the results of methacholine and mannitol inhalation challenge tests in SICT monitoring in bakers with work-related airway symptoms. Four bakery workers with a suspicion of OA underwent single-blind placebo-controlled SICTs involving workplace allergens, accompanied by the evaluation of NSBHR with mannitol and methacholine, both before and after SICTs. Clinical examinations, spirometry tests, skin prick tests (SPTs) to common aeroallergens and occupational allergens, as well as tests to determine serum specific IgE antibodies to occupational aeroallergens were also performed. Positive SPTs results to occupational aeroallergens were found in all bakery workers, and specific IgE antibodies to flour were detected in 2 subjects. Three patients displayed positive SICT reactions. In all of these 3 patients, airway responsiveness to methacholine increased significantly. In 2 patients, airway reaction to mannitol was significant, whereas in 1 subject there was no increase in NSBHR after mannitol inhalation. The patient with a negative SICT result did not reveal any changes in NSBHR before and after the test, either to methacholine or mannitol. The data obtained by the authors show that there is no clear correlation between the methacholine and mannitol inhalation challenge tests in SICT monitoring. Preliminary results indicate the need for further investigations to evaluate the usefulness of the mannitol challenge test in the diagnostics of OA. Int J Occup Med Environ Health. 2020;33(2):235-9.